Projecting South Asian Summer Precipitation in CMIP3 Models： A Comparison of the Simulations with and without Black Carbon - Li, Shuanglin; Mahmood, Rashed (Journal of Meteorological Research, 2017)
Considering the importance of black carbon （BC）, this study began by comparing the 20th century simulation of South Asian summer climate in IPCC CMIP3, based on the scenario of models with and without BC. Generally, the multi-model mean of the models that include BC reproduced the observed climate relatively better than those that did not. Then, the 21st century South Asian summer precipitation was projected based on the IPCC CMIP3 projection simulations. The projected precipitation in the present approach exhibited a considerable difference from the multi- model ensemble mean （MME） of IPCC AR4 projection simulations, and also from the MME of the models that ig- nore the effect of BC. In particular, the present projection exhibited a dry anomaly over the central Indian Peninsula, sandwiched between wet conditions on the southern and northern sides of Pakistan and India, rather than homogen- eous wet conditions as seen in the MME of IPCC AR4. Thus, the spatial pattern of South Asian summer rainfall in the future may be more complicated than previously thought.